Pregnancy dating by fetal crown-rump length: a systematic review of charts. - Napolitano, R; Dhami, J; Ohuma, E; Ioannou, C; Conde-Agudelo, A; Kennedy, S; Villar, J; Papageorghiou, A (2014)
BACKGROUND: Fetal crown-rump length (CRL) measurement by ultrasound in the first trimester is the standard method for pregnancy dating; however, a multitude of CRL equations to estimate gestational age (GA) are reported in the literature. OBJECTIVE: To evaluate the methodological quality used in studies reporting CRL equations to estimate GA using a set of predefined criteria. SEARCH STRATEGY: Searches of MEDLINE, EMBASE, and CINAHL databases, from 1948 to 31 January 2011, and secondary reference sources, were performed. SELECTION CRITERIA: Observational ultrasound studies, where the primary aim was to create equations for GA estimation using a CRL measurement. DATA COLLECTION AND ANALYSIS: Included studies were scored against predefined independently agreed methodological criteria: an overall quality score was calculated for each study. MAIN RESULTS: The searches yielded 1142 citations. Two reviewers screened the papers and independently assessed the full-text versions of 29 eligible studies. The highest potential for bias was noted in inclusion and exclusion criteria, and in maternal demographic characteristics. No studies had systematic ultrasound quality-control measures. The four studies with the highest scores (lowest risk of bias) satisfied 18 or more of the 29 criteria; these showed lower variation in GA estimation than the remaining, lower-scoring studies. This was particularly evident at the extremes of GA. AUTHOR'S CONCLUSIONS: Considerable methodological heterogeneity and limitations exist in studies reporting CRL equations for estimating GA, and these result in a wide range of estimated GAs for any given CRL; however, when studies with the highest methodological quality are used, this range is reduced.